Ambitious and anxious : how Chinese college students succeed and struggle in American higher education - Ma, Yingyi (Columbia University Press, 2020)
"In Ambitious and Anxious, the sociologist Yingyi Ma offers a multifaceted analysis of this new wave of Chinese students based on research in both Chinese high schools and American higher-education institutions. Ma argues that their experiences embody the duality of ambition and anxiety that arises from transformative social changes in China. These students and their families have the ambition to navigate two very different educational systems and societies. Yet the intricacy and pressure of these systems generates a great deal of anxiety, from applying to colleges before arriving to looking ahead upon graduation. Throughout the book, Ma sheds light on the role of class in the experiences of this relatively privileged population. Ambitious and Anxious also considers policy implications for American colleges and universities, including recruitment, student experiences, faculty support, and career services"--